2019
DOI: 10.1111/bjhp.12378
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control and health‐related behaviour: The role of implicit self‐control, trait self‐control, and lay beliefs in self‐control

Abstract: Objectives. We tested unique contribution of trait self-control, implicit self-control, and lay beliefs in self-control beliefs to the prediction of health-related behaviours. We also tested whether relations between trait self-control and health-related behaviour, and between implicit self-control and health-related behaviours, were moderated by selfcontrol beliefs.Design. Cross-sectional, correlational.Methods. Students (N = 176) completed self-report measures of trait self-control, lay beliefs that self-con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 58 publications
5
29
0
Order By: Relevance
“…Previous research has suggested that past behaviour serves to summarize the effects of habits on behaviour. Examples of these constructs might be implicitly held beliefs or individual differences that predispose individuals' impulsive behavioural patterns such as trait self-control, impulsivity, and certain personality traits (Allom et al, 2018;Hagger, Gucciardi, Turrell, & Hamilton, 2019). Habits, therefore, would be expected to mediate effects of past behaviour on subsequent behaviour, an observation found in the current study and in previous research (van Bree et al, 2015).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous research has suggested that past behaviour serves to summarize the effects of habits on behaviour. Examples of these constructs might be implicitly held beliefs or individual differences that predispose individuals' impulsive behavioural patterns such as trait self-control, impulsivity, and certain personality traits (Allom et al, 2018;Hagger, Gucciardi, Turrell, & Hamilton, 2019). Habits, therefore, would be expected to mediate effects of past behaviour on subsequent behaviour, an observation found in the current study and in previous research (van Bree et al, 2015).…”
Section: Discussionmentioning
confidence: 49%
“…It could be that the residual effect of past behaviour on HED may reflect unmeasured constructs that affect behaviour independent of intentions and other social cognition constructs. Examples of these constructs might be implicitly held beliefs or individual differences that predispose individuals' impulsive behavioural patterns such as trait self-control, impulsivity, and certain personality traits (Allom et al, 2018;Hagger, Gucciardi, Turrell, & Hamilton, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…That the only determinants of leisure-time physical activity participation in the current study were past physical activity participation, attitude, and trait self-control is consistent with this interpretation. Focusing first on the direct effect of trait self-control on behavior, this construct is proposed to reflect nonconscious processes insofar as those endorsing it are purported to exhibit adaptive self-regulatory skills that assist in pursuing goal-directed behaviors and help resist temptations to engage in alternative behaviors that may derail pursuit of the behavior [45][46][47]. On the surface, such an effect implies that individuals applying such skills must engage in active, effortful decision making to ensure focus on the target behavior and manage distractions, a conscious process.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also demonstrated that behavioral effects of trait self-control may be direct, independent of intentions [45]. Such effects reflect generalized tendencies to engage in adaptive behaviors without the need for deliberation or consideration.…”
Section: Extending the Modelmentioning
confidence: 99%
“…Trait self-control has been consistently related to adaptive behaviors, including physical activity, across multiple contexts and populations [51]. Research has also demonstrated that behavioral effects of trait self-control may be direct, independent of intentions [52]. Such effects re ect generalized tendencies to engage in adaptive behaviors without the need for deliberation or consideration.…”
Section: Extending the Modelmentioning
confidence: 99%